investigating the effect of Infodemic on the Perception and Willingness to Take the COVID - 19 Vaccine in Delta State, Nigeria - Nkonyeasua Kingsley Egun; Jude C. Igborgbor (Shahid Sadoughi University of Medical Sciences, 2022)
Introduction: The rollout of COVID-19 vaccine in response to the COVID-19 pandemic has been accompanied by infodemic. This study ascertained the influence of infodemic on individuals' willingness to be vaccinated for increased vaccine coverage in Delta State. Methods: In this cross-sectional study, 2500 respondents across the twenty five Local Government Areas in Delta State, with age of at least 15 years were selected using stratified random sampling to provide an appropriate demographic representation. A researcher - made questionnaire including demographic characteristics and questions related to participants' knowledge and attitude regarding COVID-19 vaccine was used. Descriptive Statistics of Frequency (Percentage) was used for data analysis using Microsoft Excel software version 2016. Results: Demography of respondents showed that secondary education was highest (43%), while 50% of the respondents were urban dwellers.  80.44% of the respondents admitted to the existence of the virus, while 45.84% admitted to its existence in Delta State. 27.68% of the respondents were willing to take the COVID-19 vaccine; while 58.08% declined. 63% of respondents had access to social media; and majority of them (52%) admitted to not verifying health information seen on social media with medical experts. Majority of the respondents willing to take the vaccine were aged 45 to 60 years (42.37%); reside in urban areas, have tertiary education, access to social media; and often verified health information with medical experts. Infodemic about the COVID-19 vaccine and lack of trust in the government were identified as the major debilitating factors to the public acceptance of the vaccine. Conclusion: Improving  COVID-19 vaccine coverage in Delta State requires a holistic approach of combating misinformation about the vaccine,, regulation of health information shared on the social media space, and criminalizing the act of infodemic.  Infodemic, COVID-19 vaccine, health information, social media, public health, Delta State.